Komunikasi Orang Tua Dengan Anak Di Era Digital Penelitian Studi Kualitatif Di Desa Pulungan - Putri, Zefanya Tabitha Kartono; Suprihatin, Suprihatin (LPPM Stikosa-AWS, 2024)
The communication pattern plays a crucial role in building healthy relationships, supporting child development, addressing digital challenges, building trust, and improving the quality of family life. Effective communication patterns are also a form of parental responsibility towards their children, as parents play a significant role in shaping their children's personalities, attitudes, and behaviors. In implementing good communication patterns, parents must consider the needs and development of their children and provide appropriate attention, affection, and support. The focus of this research is to identify the issues concerning the communication patterns of parents towards their children in the digital era in Pulungan Village. In this study, the author used a qualitative method to obtain descriptive data, which consists of written words and verbal expressions from the informants. To collect data, the author used a triangulation technique with an interpersonal communication approach. The interpersonal communication approach involves direct interaction between the researcher and the informants, which can be done through observation, interviews, and documentation. The research informants in this study were the secretary of Pulungan Village and parents in Pulungan Village, Sedati Subdistrict, Sidoarjo Regency. Once the data were collected, the author used data analysis techniques, including data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the role of parental communication patterns in the digital era applied by several families in Pulungan Village, Sedati Subdistrict, Sidoarjo Regency can be categorized into two main parenting patterns: pluralistic communication patterns and protective communication patterns.